2013
DOI: 10.1155/2013/690180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structure, Composition, and Micromorphology on the Hydrophobic Property of F‐DLC Film

Abstract: Fluorinated diamond-like carbon (F-DLC) films were prepared by radio frequency plasma-enhanced chemical vapor deposition technique with CF4and CH4as source gases under different deposition conditions. The chemical bonding structure and composition of the films were detected by Raman, Fourier transform infrared absorption spectrometry (FTIR), and X-ray photoelectron spectroscopy (XPS) characterization. The micromorphology and surface roughness of the film were observed and analyzed by atomic force microscopy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Coatings 2018, 8,18 decreased Ti-O bonding in the composite layer, whereas N-O increased bonding and slightly increased the Ti-N content. …”
Section: Test Results and Analysis Of The Sample Structuresmentioning
confidence: 93%
See 3 more Smart Citations
“…Coatings 2018, 8,18 decreased Ti-O bonding in the composite layer, whereas N-O increased bonding and slightly increased the Ti-N content. …”
Section: Test Results and Analysis Of The Sample Structuresmentioning
confidence: 93%
“…According to the reference [36][37][38][39], peak C1s can be Coatings 2018, 8,18 of the combination of Ti and C in XRD spectrum was found. This finding demonstrated that the major element of the composite film was TiN under the present preparation conditions and parameters.…”
Section: Test Results and Analysis Of The Sample Structuresmentioning
confidence: 94%
See 2 more Smart Citations
“…Most of those limitations can be circumvented by a modification of the DLC film, that is, by the addition of one or more elements to the film [6]. Apart from a few light elements, for example, B [7], N [8], or F [9], mainly transition metals are added for this purpose [6,10].…”
Section: Introductionmentioning
confidence: 99%